2020
DOI: 10.1101/2020.03.13.989814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective packaging of mitochondrial proteins into extracellular vesicles prevents the release of mitochondrial DAMPs

Abstract: Most cells constitutively secrete mitochondrial DNA and proteins in extracellular vesicles (EVs), small vesicles that allow the transfer of material between cells. While under pro-inflammatory conditions, this mitochondrial content can further enhance inflammation, its role in the absence of inflammation remains elusive. Here, we demonstrate that mitochondrial components found in normal EVs are not pro-inflammatory and that cells actively prevent the packaging of proinflammatory, damaged mitochondrial proteins… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…7e). It can be inferred from our western blot results and published reports (38,39) that the MV-mediated increase in recipient endothelial cell ATP levels is associated with the presence of functional mitochondria and mitochondrial proteins and their transfer into the recipient cells. High throughput proteomic analysis revealed 89 types of mitochondrial proteins in MVs vs. a single type in EXOs isolated from hCMEC/D3 cells (32).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…7e). It can be inferred from our western blot results and published reports (38,39) that the MV-mediated increase in recipient endothelial cell ATP levels is associated with the presence of functional mitochondria and mitochondrial proteins and their transfer into the recipient cells. High throughput proteomic analysis revealed 89 types of mitochondrial proteins in MVs vs. a single type in EXOs isolated from hCMEC/D3 cells (32).…”
Section: Discussionsupporting
confidence: 77%
“…We have used EVs: a natural nanocarrier, for this one, two-punch delivery strategy. EVs are known to incorporate mitochondrial components such as mitochondria, mitochondrial DNA, and proteins along with their inherent nucleic acid, lipids, and protein cargoes during their biogenesis (39,(46)(47)(48). On the other hand, endothelial overexpression of HSP27 in a transgenic mouse model of focal cerebral ischemia decreased mice brain infarct volume compared to neuronallyoverexpressed HSP27 and placebo mice (9,10,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be fascinating to address whether metabolic signalling programmes control the selective packaging and extracellular extrusion of mtDNA via exosomes. Recently, Todkar et al (2021) reported that mitochondrial derived vesicles ( Sugiura et al, 2014 ) control the incorporation of mitochondrial proteins and mtDNA into exosomes in cultured cells. Finally, what is the physiological role of regulated mtDNA release and can it be manipulated, for example in order to improve chemotherapy or treat autoimmune diseases?…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has revealed an intimate interconnection between classical autophagy machinery and autophagy-dependent EVs pathways that facilitates the disposal of unwanted genetic material and proteins (Leidal et al, 2020). Additionally, recent evidence suggests that EVs transfer mitochondrial DNA (mtDNA) and mitochondrial proteins intercellularly (Pasquale Sansone et al, 2017; Kiran Todkar et al, 2021; Xiaowan Wang et al, 2020); however, the biological relevance, the mechanisms underlying this process and the contribution in pathophysiological contexts are not clear. Neuronal-derived EVs (NDE) are a subpopulation of the central nervous system (CNS)-derived EVs that can be isolated from human fluids, including blood plasma and cerebrospinal fluid, to investigate their neuron-specific contents (Yousif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%